(untitled) (International Journal of Physiotherapy, 2021)
Background: The present study aimed to investigate the effects of Kinesiotaping on spasticity, handgrip strength, and functional activity of hand in patients with stroke. Methods: This double-blinded, placebo-controlled multi-centric study involved 20 patients with chronic stroke randomly assigned to Kinesiotaping (9 male and 1 female) and sham taping groups (7 male and 3 female). Spasticity, range of motion, handgrip strength, and hand function were measured under four conditions: (1) Without taping, (2) Immediately after application of taping, (3) 24 hours, and (4) 48 hours after taping along with conventional physiotherapy in both groups. Results: No significant differences were observed in spasticity scores, range of motion, and hand function between the two groups in all four time periods (p>0.05). Handgrip strength showed improvements immediately after taping in the kinesiotaping group (U=18.50, p=0.016) compared to the sham taping group. Conclusion: Kinesiotaping has no added benefits in reducing spasticity, improving range of motion of wrist extension, and hand function in patients with chronic stroke compared to sham taping. Despite statistical significance between groups observed in handgrip strength immediately after kinesiotaping, clinical significance of the same is not conclusive.